Early Effects of a Low Fat, Fructose-Rich Diet on Liver Metabolism, Insulin Signaling, and Oxidative Stress in Young and Adult Rats - Crescenzo, Raffaella; Cigliano, Luisa; Mazzoli, Arianna; Cancelliere, Rosa; Carotenuto, Rosa; Tussellino, Margherita; Liverini, Giovanna; Iossa, Susanna (Frontiers in Physiology, 2018)
The increase in the use of refined food, which is rich in fructose, is of particular concern in children and adolescents, since the total caloric intake and the prevalence of metabolic syndrome are increasing continuously in these populations. Nevertheless, the effects of high fructose diet have been mostly investigated in adults, by focusing on the effect of a long-term fructose intake. Notably, some reports evidenced that even short-term fructose intake exerts detrimental effects on metabolism. Therefore, the aim of this study was to compare the metabolic changes induced by the fructose-rich diet in rats of different age, i.e. young (30 days old) and adult (90 days old) rats. The fructose-rich diet increased whole body lipid content in adult, but not in young rats. The analysis of liver markers of inflammation suggests that different mechanisms depending on the age might be activated after the fructose-rich diet. In fact, a pro-inflammatory gene-expression analysis showed just a minor activation of macrophages in young rats compared to adult rats, while other markers of low-grade metabolic inflammation (TNF-alpha, MPO, lipocalin, haptoglobin) significantly increased. Inflammation was associated with oxidative damage to hepatic lipids in young and adult rats, while increased levels of hepatic nitrotyrosine and ceramides were detected only in young rats. Interestingly, fructose-induced hepatic insulin resistance was evident in young but not in adult rats, while whole body insulin sensitivity decreased both in fructose-fed young and adult rats. Taken together, the present data indicate that young rats do not increase their body lipids but are exposed to metabolic perturbations, such as hepatic insulin resistance and hepatic oxidative stress, in line with the finding that increased fructose intake may be an important predictor of metabolic risk in young people, independently of weight status. These results indicate the need of corrective nutritional interventions for young people and adults as well for the prevention of fructose-induced metabolic alterations.